An Analysis Of Sodium Cyclamate Sweetener On Doger Ice Drink In Padangsidimpuan - susilawati harahap (Hikamatzu | Journal of Multidisciplinary, 2026)
Sodium cyclamate is a synthetic sweetener that has some special characteristics such as white, odorless, and crystal powder. Based on the regulation Permenkes number 208\1985, the use of sodium cyclamate may not be over 3 mg. The sample is doger ice. There are 10 samples of doger ice which taken from the merchants in Padangsidimpuan. Additionally, The samples are analyzed by qualitative and quantitative analysis. Qualitative analysis uses the solution of HCl 10%, BaCl2 10%, NaNO2 10% whereas quantitative analysis uses the gravimetric method. As a result, from 10 samples of doger ice are found 2 positive samples that contain sodium cyclamate. First, sample B contains 1,9 gfood. Second, sample G contains 1, 94 gfood. However, it states that this amount is still safe to consume because it is not over from the standard because it is still in a normal amount. To sum up, the government and society should improve controlling about the use of synthetic sweetener